2024
DOI: 10.3390/biomedicines12051058
|View full text |Cite
|
Sign up to set email alerts
|

Botulism Cases in Romania—An Overview of 14-Year National Surveillance Data

Andreea Marilena Păuna,
Maria-Dorina Crăciun,
Anca Sîrbu
et al.

Abstract: Botulism is a priority disease worldwide because it has a very severe course of evolution that can lead to death. This paper aims to describe the main epidemiological characteristics of botulism cases confirmed in Romania over 14 years (2007–2020). We performed a retrospective study using the publicly available national surveillance data and reported to the National Institute of Public Health. A total of 325 cases of foodborne botulism were reported in Romania, with no infant or wound botulism. Most of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Initially considered to be a fungus, it was only between 1895 and 1897 that it was demonstrated that botulism was caused by the toxin of an anaerobic bacillus, known as Bacillus botulinus. During this same period, using a cell culture filtrate, free of bacilli and spores, signs of paralysis were reproduced in laboratory animals, confirming the existence of a toxin [12][13][14] Currently called Clostridium botulinum, this anaerobic bacillus is classified into seven types (A, B, C, D, E, F and G), based on the antigenic specificity of the neurotoxin (BoNT) produced by each strain. Encoded by the BoNT gene, these toxins are produced as 150 kDa polypeptide chains, which are cleaved into two smaller chains, prior to release by the microorganism.…”
Section: Botulismmentioning
confidence: 69%
See 3 more Smart Citations
“…Initially considered to be a fungus, it was only between 1895 and 1897 that it was demonstrated that botulism was caused by the toxin of an anaerobic bacillus, known as Bacillus botulinus. During this same period, using a cell culture filtrate, free of bacilli and spores, signs of paralysis were reproduced in laboratory animals, confirming the existence of a toxin [12][13][14] Currently called Clostridium botulinum, this anaerobic bacillus is classified into seven types (A, B, C, D, E, F and G), based on the antigenic specificity of the neurotoxin (BoNT) produced by each strain. Encoded by the BoNT gene, these toxins are produced as 150 kDa polypeptide chains, which are cleaved into two smaller chains, prior to release by the microorganism.…”
Section: Botulismmentioning
confidence: 69%
“…The origin of the BoNT gene varies between types of C. botulinum: types A, B, E and F, which cause human botulism, are of chromosomal origin; types C and D, responsible for the vast majority of cases of the disease in animals, originate from bacteriophages; For type G, the origin is plasmid. .Interventionary studies involving animals or humans, and other studies that require ethical approval, must list the authority that provided approval and the corresponding ethical approval code [1,5,8,[12][13][14].…”
Section: Botulismmentioning
confidence: 99%
See 2 more Smart Citations